Proceedings of the 5th Global Conference on Business, Management and Entrepreneurship (GCBME 2020) 2021
DOI: 10.2991/aebmr.k.210831.104
|View full text |Cite
|
Sign up to set email alerts
|

UTAUT2 Analysis on the Use of On-Demand Services Application with Perceived Privacy as Moderating Effect

Abstract: Indonesia has a large population and the growth of smartphone users in recent years defines a potential market for digital products. Establishment of the internet and technology advances creates innovations in various industry that allow consumers to access product and services easily and seamlessly. As consumer behavior is changing, digital service provider develops an online platform, which can be accessed anytime and anywhere, to fulfill consumer's needs and wants in the form of On-Demand Services applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Notably, the study emphasized the importance of privacy concerns, privacy risk, and perceived information control in vehicular app acceptance, suggesting measures that enhance personal information control (Walter & Abendroth, 2020). Similarly, Noraga et al (2021) observed that perceived privacy influenced consumer acceptance of on-demand services due to concerns over personal information exchange (Noraga et al, 2021). Integrating informational privacy variables such as privacy concerns, privacy risk, and perceived information control should lead to relevant findings in the context of ODCF acceptance.…”
Section: Moral-normative System Evaluationmentioning
confidence: 86%
See 1 more Smart Citation
“…Notably, the study emphasized the importance of privacy concerns, privacy risk, and perceived information control in vehicular app acceptance, suggesting measures that enhance personal information control (Walter & Abendroth, 2020). Similarly, Noraga et al (2021) observed that perceived privacy influenced consumer acceptance of on-demand services due to concerns over personal information exchange (Noraga et al, 2021). Integrating informational privacy variables such as privacy concerns, privacy risk, and perceived information control should lead to relevant findings in the context of ODCF acceptance.…”
Section: Moral-normative System Evaluationmentioning
confidence: 86%
“…Other potential endogenous or exogenous mechanisms toward driver's acceptance of ODCFs are security (Garidis et al, 2020), complexity (J. Kim et al, 2016), accessibility (N. Kim et al, 2019), uniqueness (Vafaei-Zadeh et al, 2021), visual attractiveness (Yoon & Cho, 2016), and immediacy (Noraga et al, 2021). Nastjuk et al (2020) explored autonomous driving acceptance using a TAM-based design, highlighting enjoyment as a key determinant with a positive correlation to perceived ease of use (Nastjuk et al, 2020).…”
Section: Entrepreneurship and Sustainability Issuesmentioning
confidence: 99%